Metagenomic approaches to understanding bacterial communication during the anammox reactor start-up. (1st June 2018) - Tang, Xi; Guo, Yongzhao; Jiang, Bo; Liu, Sitong
Abstract: Increasing attention has been paid to the anammox community for its significant function in high-efficiency wastewater treatment. However, bacterial interaction in terms of bacterial communication is still elusive. This study firstly explored the intra- and interspecific communication of bacteria in the anammox community using metagenomic sequence data obtained during bioreactor operation. We verified the existence of multiple bacterial communication gene (BCG) subtypes by alignment with the constructed BCG database containing 11 identified gene subtypes. Bacterial communication was more active at the initial start-up than in the high loading-rate phase, and was correlated with the gradually decreasing bacterial diversity. Hdts, one of the key genes that produced the intraspecific signaling molecule AHL, and RpfF, the key gene that produced the intra- and interspecific signaling molecule DSF, were the primary communication engines in the anammox community because of their high abundance. Anammox bacteria mainly used Hdts genes to communicate with others, while RpfF gene played a core role characterized by their multiple correlations with other BCG subtypes. Interestingly, bacteria with abundant BCGs were more inclined to interact with the bacteria with the same functional traits, indicating the potential communication-related interaction among these bacteria in addition to the frequently reported substrate co-utilization. This highlights the primary importance of AHL and DSF for the anammox community, and thereby hints at a potential strategy for the target regulation of the signals to improve anammox viability and competitive capacity in wastewater treatment. Graphical abstract: Highlights: Intra- and interspecific bacterial communication in anammox culture are verified. HdtS and RpfF genes are important engines for communication during start-up. Anammox bacteria use HdtS genes to communicate. RpfF genes plays a core role in intra- and interspecific species communication. Bacteria are inclined to communicate with other bacteria with the same function.